Isolation of cardamonin, pinostrobin chalcone from the rhizomes of Boesenbergia rotunda and their cytotoxic effects againts colon cancer HT29 and breast cancer MDA-MB-231 cell lines - Mohammed, Ibrahim Awad (2019)
Boesenbergia rotunda is an example of medicinal herbal plants which has been traditionally employed in the treatment of many life-threatening ailments such as diuretic, dysentery, inflammation, aphrodisiac and gastrointestinal disorder. Natural products from medicinal plants, either as pure compounds or as standardized extracts, provide unlimited opportunities for new drug leads because of the huge availability of chemical diversity. Due to an increasing demand for chemical diversity in screening programs, seeking therapeutic drugs from natural products, interest particularly in edible plants has grown throughout the world. In this study bioactive compounds were extracted and thereafter isolated from the root of Boesenbergia rotunda using solvent extraction techniques. The synthesized compounds were characterized by using UV-Visible, Fourier Transform Infrared spectrophotometry (FTIR), Gas Chromatography-Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance (NMR) spectrometry. The extracts were thereafter subjected to cytotoxic analysis to study the biological activities of the extracts. The bioactive extracts hexane and chloroform extracts were subjected to column and thin chromatography. Six major chemicals constituents, pinostrobin (1), pinostrobin chalcone (2), cardamonin (3), 4,5-dihydrokawain (4) pinocembrin (5), and alpinetin (6) were isolated from the rhizomes of the Boesenbergia rotunda. All the chemical constituents were screened against the human triple-negative breast cancer cell (MDA-MB-231) and HT-29 colon cancer cell lines by using 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay in vitro. The compound cardamonin (3), (IC50 = 5.62±0.61 and 4.44±0.66 μg/mL) and pinostrobin chalcone (2), (IC50 = 20.42±2.23 and 22.51±0.42 μg/mL) were found to be potential natural cytotoxic compounds against MDA-MB-231 and HT-29 colon cancer cell lines, respectively. Cytotoxic effects of cardamonin (3), pinostrobin chalcone (2) and flavokawain B (FKB) were also compared and visualized by the molecular docking studies to establish the structure-activity relationship. The structures of all compounds were supported with the aid of 1H-NMR, GC-MS, IR, UV and single X-ray crystallographic techniques. These findings could help to improve the future drug discovery against breast cancer and colon cancer cell lines (H29). The result of the study suggests that B. rotunda rhizome has a potential in drug and nutraceutical applications. Moreover, this provides a baseline information on the presence of the compounds produced in in vitro cultures which is crucial for further manipulation of the metabolic pathway in other relevant studies